Research on ecological compensation of coupling improved ecosystem service value-ecological footprint model in Shaanxi Province, China - Wei, Junhua; Wei, Na; Lu, Kunming; Zhang, Xiao; Zhang, Lei; Gao, Fei; Ji, Kaixuan; Yang, Yujin (Frontiers in Environmental Economics, 2025)
IntroductionAs a typical ecologically fragile area, Shaanxi Province has a prominent contradiction between sustainable economic development and ecological environmental protection, and ecological compensation is needed. Existing studies predominantly focus on single ecosystems, often neglecting the supply-demand relationship between human and nature, the ability to pay compensation amount and the economic development level at the same time, resulting in poor operability.MethodsIn view of this, this paper introduces the adjustment coefficient of payment capacity and the adjustment coefficient of economic level to modify ecosystem service value (ESV). By coupling the improved ESV and ecological footprint model, the ecological compensation amount of Shaanxi Province was calculated.ResultsThe results show that: (1) The improved ESV of Shaanxi Province in 2022 was 6.174 billion CNY. Among them, the ESV of forest and water area were as high as 4.884 billion CNY and 485 million CNY, respectively, accounting for 86.98% of the total ESV. In addition, the value of regulating service accounted for the largest proportion of ESV in all services, reaching 68.7%. (2) The ecological footprint (EF) of Shaanxi Province in 2022 was 134.2669 million hectares but the total ecological carrying capacity (ECC) was 14.262 million hectares. The ecosystems with the most serious ecological deficit were fossil energy land and farmland. (3) The ecological overload index (EFI) of Shaanxi Province in 2022 was −8.41, which means that the resources of the whole province were seriously in short supply.DiscussionAs the payer of ecological compensation, the amount of compensation was 51.947 billion CNY. This study comprehensively considers the supply-demand relationship between human and nature, regional payment capacity and economic development level, so that the proposed ecological compensation scheme can better meet the actual needs and has strong operability, which provides a valuable reference for implementing ecological compensation and advancing environmental protection in Shaanxi Province.